NATURE AND SPACE IN ANDREY BITOV'S NOVEL ARMENIAN LESSONS - Kamilya Azimovna Nabiyeva (Web of Journals Publishing, 2024)
Lessons of Armenia’ by Andrei Bitov is a story that was conceived by the writer in the late 60s, in a difficult period of creative self-determination and search for himself. Spaciousness is a necessary condition for the perception of Armenia. Much of what A. Bitov talks about in the story coincides with the ideas of D.S. Likhachev. Spaciousness is a special category that allows us to feel the character of the people, which combines the natural, religious and creative origins. This aspect is not accidentally revealed with the help of reminiscences from Pushkin's and Tyutchev's poems. As the task of the traveller is not only to explore Armenia, but also to return to his own national identity and creativity.
Keywords: novella, Russian literature, world picture, space, time, chronotope, Andrei Bitov.